Culture and tourism: Reappropriation of their relationships from an epistemic thought based on inclusion and sustainability (Ágora de Heterodoxias, 2024)
The essay is structured around contemporary tourism and its impact on the local culture and lifeworld of tourist destinations. The proposed thesis is: the tourism industry disguises local culture and incorporates it into tourist development with an internationalist vision, following the criteria of a globalized cultural industry that disdains the location and the culture that is inherent to it. Paradigmatic categories (human development, local development, sustainable development) and theoretical categories (local culture, identity, territoriality, world of life, inclusion and popular education) are discussed, considered fundamental to rethink "other" modes and aesthetics of tourism development, capable of ovaluing and incorporating, in its essence, the culture and life worlds close to the subjects who dynamize it. Methodologically, the foundations of interpretivism are addressed (Sandín 2003 and Rusque 2003), therefore, the essay emerges configured in the interactions between the narratives of the consulted authors, and the academic and tourist experiences of the writers, always linked to the phenomenology represented by Margarita Island, the main Venezuelan tourist destination. The essay defends a sensitivity and aesthetics of tourist development, whose axis is constituted by local culture within the framework of a social and tourist imaginary of sustainability and community inclusion.
Keywords: Tourism Industry; Tourism Development; Local Culture; Community and Sustainability